Evaluation of Records Management System of the Road Maintainance in the Ministry of Works, Housing and communication's Headquaters : a case study, tororo - Achieng, Rachael (Mukono : Uganda Christian University, 2009)
Descriptive Cataloguing Uganda Christian University BLIS
Includes appendix and references
Keywords: Evaluation of Records Management